Priorities for realizing the potential to increase agricultural productivity and growth in Western and Central Africa - Nin-Pratt, Alejandro; Johnson, Michael E.; Magalhaes, Eduardo C.; Diao, Xinshen; You, Liangzhi; Chamberlin, Jordan (International Food Policy Research Institute, 2009)
We identify a set of development priorities for agriculture that cut across West Africa, at both the country and the regional level, to achieve economy-wide growth goals in the region. To do this, we adopt a modeling and analytical framework that involves the integration of spatial analysis to identify yield gaps determining growth potential of different agricultural activities for areas with similar conditions and an economy-wide multimarket model to simulate ex ante the economic effects of closing these yield gaps. Results indicate that the greatest agriculture-led growth opportunities in West Africa reside in staple crops (cereals as well as roots and tubers) and livestock production. Rice is the commodity with the highest potential for growth and the one that could generate the greatest benefits for many countries. Activities contributing the most to agricultural growth in the Sahel are livestock, rice, coarse grains, and groundnuts; in coastal countries, staple crops like cassava, yams, and cereals seem to be relatively more important than the contributions of other subsectors; and livestock and root crops are the sources of growth with highest potential in Central Africa. Our results also point toward an essential range of policies and investments that are needed to stimulate productivity growth of prioritized activities. These include the following: development of opportunities for regional cooperation on technology adaptation and diffusion, strengthening of regional agricultural markets exploiting opportunities for greater regional cooperation and harmonization, diversification of traditional markets, and enhancement of linkages between agricultural and nonagricultural sectors.